Taṭwīr Al-Wasāil At-Ta‘līmiyyah Ar-Raqmiyyah At-Tafā‘uliyyah bistikhdām mauqi‘ CANVA Fī Ḍau‘I Naẓariyyah Al-Bināiyyah li-Jean Piaget Litarqiyyati Mahārah Al-Istimā‘: Developing interactive digital educational tools using the Canva website in light of Jean Piaget’s constructivist theory to improve listening skills - Ipmafa, Muhamad Alaa Uddin; Ipmafa, Sahal Mahfudz; Ipmafa, Ali Subhan (Universitas Negeri Semarang, 2024)
This research aims to: 1) Know the educational means of teaching Arabic at the Islamic High School Rawdat Al-Talibin Taiyo Baty. 2) Design and develop interactive digital educational means using the Canva website in light of Jean Piaget's constructivist theory to improve students' listening skills at the Islamic High School Rawdat Al-Talibin Taiyo Baty. 3) Know the effectiveness of interactive digital educational means using the Canva website. The type of research used by the researcher is Research & Development (R&D) with the design of the ADDIE model (analysis, design, development, implementation, evaluation). Data were collected through observation, interviews, and tests (pre-test and post-test) using tools like observation sheets, questionnaires, and tests. Data analysis uses descriptive statistics and t-tests to measure the effectiveness of the methods. The research was conducted in the tenth grade of Rawdat Al-Talibin Taiyo Baty Islamic High School with a sample of 30 students. The results of the material experts’ verification gave a score of 85 (outstanding category), and the media experts gave a score of 78, indicating slight improvements. These teaching methods significantly improved the student’s listening skills, with an average pre-test score of 67.46 and the post-test score of 90.14, marking an increase of 22.67 points. The t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the pre-test and post-test results. These were considered. The methods are effective and have received positive responses from students and teachers, with recommendations for minor improvements before further implementation.